The COVID-19 infodemic through facebook: comparison of content and the accuracy of breastfeeding information - Mohd Shukri, Nurul Husna; Mohd Sobri, Nursaleha; Mohd Shukri, Siti Rohkmah (Springer, 2022)
Background: The coronavirus disease (COVID-19) pandemic has resulted in a significant increase in the number of people seeking online support and information, particularly on social media. Nevertheless, the nature and trend of internet information, as well as its accuracy, are questionable. This study aimed to assess and compare the content, type/form, and degree of accuracy of breastfeeding information on Facebook before and during the COVID-19 pandemic (n = 288/phase). Methodology: The data were gathered from Malaysian public and group/page Facebook posts (n = 456). Keyword searches were conducted using Malay and English breastfeeding terms. The dataset was screened and entered into a structured codebook. The Delphi approach was used to assess the accuracy of posts’ content performed by breastfeeding experts. Results: Sharing personal experience (53.2%) was the most common topic in breastfeeding-related posts, followed by seeking questions (39.3%) and knowledge (8.0%). Sharing personal stories and knowledge posts were higher during COVID-19 than before (p = 0.001), although the seeking questions category was higher before the pandemic (p = 0.001). Most information posted was in text form (94.5%). About half of the posts (46.5%) were misleading, while (43.7%) were accurate. There was a significant difference in the accuracy of online posts before and during the COVID-19 pandemic (p = 0.001). Conclusions: Compared to the pre-pandemic phase, forms/types of information on Facebook remained consistent, whereas the breastfeeding information content and its degree of accuracy differed during the pandemic.We need to explore other aspects of breastfeeding online content as well as its engagement, especially during a pandemic. Knowing the infant feeding-related topics that have been discussed and questioned on social media, as well as the accuracy of the data, allows policymakers and scientific communities to plan strategies for spreading credible breastfeeding information online. This includes creating interactive online media types of visual guidelines, web resources, and breastfeeding apps.